AEDES AEGYPTI (L.) SURVIVAL AFTER EXPOSURE TO IVERMECTIN - Simmons, Cameron (2018)
Ivermectin has been shown in in vitro studies to have insecticidal properties against Aedes aegypti adults. This study aimed to assess these properties in vivo. Aedes aegypti survival was not affected by acquiring a blood meal from humans both 5 hours and 24 hours after ingestion of a typical dose of ivermectin.